Weight loss expectations and body dissatisfaction in young women attempting to lose weight. (19th April 2013) - Siervo, M.; Montagnese, C.; Muscariello, E.; Evans, E.; Stephan, B. C. M.; Nasti, G.; Papa, A.; Iannetti, E.; Colantuoni, A.
Abstract: Background: Unrealistic weight loss expectations (WLEs) and greater body dissatisfaction may be associated with the poor long‐term outcomes of dietary and lifestyle weight loss treatments. We evaluated the association between body size, WLEs and body dissatisfaction in young women attempting to lose weight. Methods: Forty‐four young healthy women [age range 18–35 years, body mass index (BMI) range 23–40 kg/m 2 ] were recruited. Women were classified as obese (BMI ≥ 30.0 kg/m 2 ) and non‐obese (BMI <30.0 kg/m 2 ). The Body Dissatisfaction scale of the Eating Disorder Inventory‐2 and the Body Image Assessment for Obesity silhouette charts were used to assess body dissatisfaction. WLEs were categorised according to personal (ideal, happiness, satisfaction, weight history), lifestyle (fitness) and social (career, family acceptance, peer acceptance, mass media, social pressure) factors. Individual WLEs were compared with recommended clinical targets (5%, 10% and 20%) for weight loss. Results: Body dissatisfaction was lower in non‐obese subjects and was directly associated with BMI ( P  < 0.05). WLEs were directly associated with BMI and the obese group reported greater expectations. Five non‐obese subjects (23%) desired to lose more than 20% of their body weight, whereas the proportion was significantly higher in the obese group (17 subjects; 74%). Subjects derived the greatest WLEs from mass media, whereas they perceived that family and friends were supportive of a lesser degree of weight loss. Conclusions: We observed a mismatch between clinical and personal expectations, and social pressure and interpersonal relationships appear to have a prominent role with respect to influencing the association.